Global patterns and determinants of bacterial communities associated with ectomycorrhizal root tips of Alnus species - Aslani, Farzad; Tedersoo, Leho; Põlme, Sergei; Knox, Oliver; Bahram, Mohammad (Soil biology & biochemistry, 2020)
Plant-soil interactions affect plant health, productivity and vegetation structure. Although recent advances in sequencing and computational tools have facilitated research on these complex interactions, we still have a poor understanding of the relative influence of biotic and abiotic factors on their community assembly. Here we aimed to determine the relative contributions of Alnus species and their associated mycorrhizal fungi, spatial, edaphic and climatic factors to the structure of root-associated bacterial communities. We used high-throughput identification of bacteria based on 369 ectomycorrhizal root tips of 19 Alnus species from 85 sites across the globe. We found that the Alnus species phylogeny was the primary determinant for the composition of root-associated bacterial communities, followed by edaphic, spatial and climate variables. Moreover, we observed Alnus species-specificity for some highly abundant bacterial phylotypes. These results reflect the importance of biotic variables in shaping root-associated bacterial communities and suggest that different processes underlie root-associated and soil bacterial communities on a global scale. •Phylogenetically distant Alnus species harbored dissimilar bacterial communities.•Biotic variables had stronger effects on the assembly of bacterial communities.•Some highly abundant bacterial phylotypes showed Alnus species-specificity.